Equilibrium real exchange rates, misalignment and competitiveness in the Southern Cone - Montiel, Peter J. (CEPAL SantiagoCL, 2007)
Presents an analysis of the evolution of the competitiveness in the traded goods sectors in six Latin American countries. Finds that the competitiveness of the nontraditional traded goods sector has evolved in different ways among these countries during recent years.